Efficiency of intraoperative neuromonitoring on voice outcomes after thyroid surgery. Issue 5 (October 2017) - Baek, Seung-Kuk; Lee, Kijeong; Oh, Dongju; Kang, Sung Hoon; Kwon, Soon-Young; Woo, Jeong-Soo; Cho, Jae-Gu; Oh, Kyung Ho; Lee, Doh Young; Jung, Kwang-Yoon
Abstract: Objective: Voice disturbance is an important problem after thyroidectomy. The aim of this study was to evaluate the efficiency of intraoperative neuromonitoring (IONM) in reducing early phonation change by comparing postoperative voice outcomes. Methods: The study retrospectively enrolled 68 consecutive female patients who had undergone IONM thyroidectomy for papillary thyroid carcinoma occurring between January 2014 and November 2014. A historical group of 117 similar female patients not receiving IONM thyroidectomy was used as an external control. Voice analyses were performed preoperatively and at 1 week, 1 month, and 3 months postoperatively. Voice outcomes between the IONM group and no IONM group were compared in patients who underwent hemithyroidectomy and total thyroidectomy. Results: In patients who underwent IONM, there were significantly smaller changes in the fundamental frequency at postoperative 1 month and in the maximum voice pitch of the voice range profile at postoperative 1 week irrespective of the extent of thyroid surgery. Conclusion: IONM during thyroid surgery resulted in better outcomes regarding fundamental frequency and high-pitch voice in the early postoperative period. IONM appears to be an effective method to reduce temporary phonation alteration after thyroid surgery.